This man's pill : reflections on the 50th birthday of the pill - Djerassi, Carl (Oxford University Press, 2001)
"October 15, 1951 marks the birthday of one of the key episodes in 20th century social history: the first synthesis of a steroid oral contraceptive in a small laboratory in Mexico City - an event that triggered the development of the Pill. Carl Djerassi has been honored world-wide for that accomplishment, which ultimately changed the life of women and the nature of human reproduction in ways that were not forseeable. On the 50th anniversary of this pivotal event, Djerassi weaves a compelling personal narrative full of self-reflection and occasional humour on the impact this invention has had on the world at large and on him personally. He credits the Pill with radically altering his academic career at Stanford University to become one of the few American chemists writing novels and plays."